2016
DOI: 10.1515/msr-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Torso Model Complexity on the Noninvasive Localization of Ectopic Ventricular Activity

Abstract: Location of premature ectopic ventricular activity was assessed noninvasively in five patients using integral body surface potential maps and inverse solution in terms of a single dipole. Precision of the inverse solution was studied using three different torso models: homogeneous torso model, inhomogeneous torso model including lungs and heart ventricles and inhomogeneous torso model including lungs, heart ventricles and atria, aorta and pulmonary artery. More stable results were obtained using the homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In the clinical practice, where the noise is unavoidable part of the measurement, the selected time interval representing ectopic activity should be of longer duration. Nevertheless, our study in patients [15] had shown that using this method and increasing the time interval for IBSPM computation up to 15 ms allows to localize the PVC origin with a LE within 2 cm. As the obtained mean LE using noise-free input data was about 5-6 mm, the study also suggests that smaller grid dimension for the possible positions of the PVC origin would probably not improve the accuracy of the method.…”
Section: Critical Success Factorsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the clinical practice, where the noise is unavoidable part of the measurement, the selected time interval representing ectopic activity should be of longer duration. Nevertheless, our study in patients [15] had shown that using this method and increasing the time interval for IBSPM computation up to 15 ms allows to localize the PVC origin with a LE within 2 cm. As the obtained mean LE using noise-free input data was about 5-6 mm, the study also suggests that smaller grid dimension for the possible positions of the PVC origin would probably not improve the accuracy of the method.…”
Section: Critical Success Factorsmentioning
confidence: 87%
“…To solve this issue, regularization methods limiting the mathematical model are used [12][13][14]. In the case of PVC origin, a small activated region is localized and the cardiac generator can be modeled by a single dipole [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that if the PVC starts in one position in the ventricle then during the initial phase of activation only small area is depolarized, that can be represented by a single equivalent heart generator. This approach was used in [4] for DIPs. In presented study the approach was used for all available generators.…”
Section: Methodsmentioning
confidence: 99%
“…The reconstructed generator is usually computed in the form of epicardial potentials, transmembrane voltages or equivalent double layer [2], [3]. In [4] a single dipole was reconstructed. Because the inverse problem is ill posed, various regularization methods are tested and computational aspects are studied [5] to receive stable and physiological results.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past four decades, ECGI has seen considerable development, from purely analytical studies ( Rudy et al, 1979 ; Figuera et al, 2016 ; Svehlikova et al, 2018 ), to torso tank ( Oster et al, 1997 , 1998 ; Ramanathan and Rudy, 2001 ; Shome and Macleod, 2007 ; Bear et al, 2018a ) and large animal models ( Liu et al, 2012 ; Oosterhoff et al, 2016 ; Cluitmans et al, 2017 ; Bear et al, 2018b ) and finally application in humans ( Ghanem et al, 2005 ; Horáček et al, 2011 ; Haissaguerre et al, 2014 ; Schulze, 2015 ; Punshchykova et al, 2016 ). It is now increasingly used for academic research and in clinical practice.…”
Section: Introductionmentioning
confidence: 99%